2020
DOI: 10.1111/tbed.13604
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and clinical characteristics of 333 confirmed cases with coronavirus disease 2019 in Shanghai, China

Abstract: Coronavirus disease 2019 (COVID-19) is an emerging infectious disease first identified in Wuhan City, Hubei Province, China. As of 19 February 2020, there had been 333 confirmed cases reported in Shanghai, China. This study elaborates on the epidemiological and clinical characteristics of COVID-19 based on a descriptive study of the 333 patients infected with COVID-19 in Shanghai for the purpose of probing into this new disease and providing reference. Among the 333 confirmed cases in Shanghai, 172 (51.7%) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
2
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 35 publications
5
54
2
3
Order By: Relevance
“…The Centers for Disease Control and Prevention (CDC) sug- were different from those we observe in the United States (Chen et al, 2020;Yu et al, 2020). Of particular concern is the Hispanic/ Latino population where significant disparities exist (Laurencin & McClinton, 2020).…”
Section: Differences In Clinical Characteristics Of Covid-19 In Hispacontrasting
confidence: 64%
“…The Centers for Disease Control and Prevention (CDC) sug- were different from those we observe in the United States (Chen et al, 2020;Yu et al, 2020). Of particular concern is the Hispanic/ Latino population where significant disparities exist (Laurencin & McClinton, 2020).…”
Section: Differences In Clinical Characteristics Of Covid-19 In Hispacontrasting
confidence: 64%
“…The median time from illness onset to death was 24 days (IQR 6-17), whereas the median time from illness onset to discharge was 38 days (IQR 21-33). The similar trend was shown in hospital length of stay (11)(12)(13)(14)(15)(16)(17) vs. [25][26][27][28][29][30][31][32][33]). Consistent with discharge standers, viral shedding of survivors was happened during treatment course.…”
Section: Treatment and Outcomessupporting
confidence: 62%
“…The SARS outbreak in 2003 revealed that knowledge, attitude, and practice (KAP) play equally important roles in the prevention and control of an outbreak. Therefore, many researchers have conducted surveys to investigate the outbreak-related KAP of the general public in China during the outbreak in order to identify gaps for prevention and control and provide a theoretical basis for the development of targeted prevention and control measures [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%